Event Tourism in the Tourist Offer of the City of Sarajevo - Topalović, Ena; Čaušević, Amra (Journal for Geography, 2022)
The purpose of this paper is to analyse event tourism in the tourist offer of the City of Sarajevo, i.e., to what extent does event tourism in the tourist destination of the Sarajevo Canton affects the increase or decrease in demand for the destination, and the economic and social significance of the various events, present or past, for the Sarajevo Canton. The paper used a quantitative research approach, which included data collection through an online survey (Google Forms). The research was conducted from September 1st until September 11th in year 2021, on a convenience sample of 40 respondents. The survey consisted of two parts, where the first one is related to the demographic characteristics of the respondents, while the second part was based on the satisfaction with the quality of the offer of tourist events in Sarajevo and on the interest of tourists in the development of potential events in Sarajevo (Advent). The methods of analysis, synthesis, and descriptive statistics were used to interpret the obtained data.
Keywords: Event tourism; events; Sarajevo; tourism; tourist offer